Flexible Learning in Higher Education Institution: Experiences of Instructors in a Private Higher Institution - Cachero–Paderog, Jane (JPAIR Multidisciplinary Research, 2023)
This research investigates instructors' experiences at Agusan del Sur College concerning Flexible Learning in the New Normal. The study adopts a mixed-method approach integrating quantitative and qualitative components. Participants are 30 full-time instructors across nine departments. The findings reveal that instructors need more training and technical competencies to conduct online courses, affecting the effectiveness of hybrid classes. Technical problems, including slow internet connections and unannounced power interruptions, despite these challenges, instructors value the flexibility inherent in Flexible Learning, spanning modalities, assessment methods, and instructional delivery, promoting greater student responsibility and time management, ultimately enhancing engagement and attentiveness. Moreover, smartphones and mobile applications serve as prevalent educational tools and eLearning resources, and there remains a preference for face-to-face classes over online learning. The study also underscores the positive impact of Flexible Learning, encompassing synchronous and asynchronous platforms, in enhancing digital and technological competencies, with 45.4% of students and 48.8% of instructors reporting its benefits. Additionally, instructors with 0-5 years of teaching experience exhibit excellent proficiency in Flexible Learning modalities and assessment methods. In conclusion, this research suggests that Flexible Learning could constitute a sustainable mode of delivery in higher education institutions, contingent on instructors receiving adequate training and support to navigate the challenges the New Normal poses effectively.
Keywords: face-to-face; hybrid; assessment methods; flexible learning; new normal; mixed-methods; Philippines